Prevalence of asthma-like symptoms, asthma and its treatment in elite athletes - Lund, T.; Pedersen, L.; Larsson, B.; Backer, V. (Scandinavian Journal of Medicine & Science in Sports, 2009)
The objective was to determine the prevalence of asthma-like symptoms and asthma and the use of asthma medication in Danish elite athletes. A cross-sectional questionnaire survey of Danish elite athletes was conducted in 2006. All elite athletes (N=418) financially supported by the national organization of elite athletes comprised the study group; 329 (79%) completed the questionnaire concerning their sport, asthma-like symptoms, asthma and use of asthma medication. Asthma-like symptoms at rest were reported by 41% of respondents; 55% reported asthma-like symptoms at rest or at exercise. Physician-diagnosed asthma was present in 16% and 14% had current asthma. Asthma medication was taken by 7% of the athletes, of whom 79% used inhaled corticosteroids and 21% used inhaled ß2-agonists only. Athletes participating in endurance sports had higher prevalences of current asthma (24%) and use of asthma medication (15%) than all other athletes (P<0.01). Athletes participating in endurance sports have a higher prevalence of asthma and use of asthma medication. The frequency of asthma medication is lower than the prevalence of current asthma indicating that there is no overuse of asthma medication among Danish elite athletes.